Representation of The "Indonesia Gelap" Demonstration at The Horse Statue in Jakarta: A Comparative Analysis of CNN Indonesia and Kompas Coverage - Mohamad Andrianto; Latif Ahmad Fauzan (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
Demonstrations are an important mechanism for the public to voice their aspirations and criticisms, where the mass media plays a fundamental role in shaping public perception of these kinds of events. This study aims to analyze the representation of the "Indonesia Gelap" demonstration at the Jakarta Horse Statue through a comparison of the coverage of two major digital media, CNN Indonesia and Kompas.com. This study seeks to identify and interpret the differences in framing applied by the two media, as well as understand their implications for the construction of reality and societal understanding. Using Robert N. Entman's framing analysis method, this study identifies how the two media define the problem, diagnose the causes, make moral judgments, and propose solution recommendations. The results showed significant differences in framing; CNN Indonesia tends to highlight security aspects and potential for unrest, while Kompas.com focuses more on the substance of student demands and dialogue efforts. These differences reflect how the media actively constructs narratives that can influence public perception and opinion.